2018
DOI: 10.1080/14767058.2018.1524457
|View full text |Cite
|
Sign up to set email alerts
|

Does left ventricular hypertrophy by electrocardiogram predict adverse outcomes in pregnancies with chronic hypertension?

Abstract: LVH by ECG criteria may be associated with higher rates of SIP and with lower birthweight in pregnancies with CHTN. ECG may be a cost-effective tool to identify patients with CHTN at risk of adverse outcomes. Larger trials are necessary to corroborate our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 12 The 2016 Asian Expert Consensus on the Diagnosis and Treatment of Hypertension and Left Ventricular Hypertrophy clearly pointed out that an electrocardiogram is the first choice for screening and diagnosing hypertension and left ventricular hypertrophy. 13 The results of this study showed that, compared with the Control group, patients in the Study group had statistically significant differences in body surface area, heart rate, diastolic blood pressure, systolic blood pressure, left ventricular muscle weight index, left ventricular posterior wall thickness, and interventricular thickness, suggesting that the elderly patients with essential hypertension and LVH may have the basis of abnormal ECG results.…”
Section: Discussionmentioning
confidence: 68%
“… 12 The 2016 Asian Expert Consensus on the Diagnosis and Treatment of Hypertension and Left Ventricular Hypertrophy clearly pointed out that an electrocardiogram is the first choice for screening and diagnosing hypertension and left ventricular hypertrophy. 13 The results of this study showed that, compared with the Control group, patients in the Study group had statistically significant differences in body surface area, heart rate, diastolic blood pressure, systolic blood pressure, left ventricular muscle weight index, left ventricular posterior wall thickness, and interventricular thickness, suggesting that the elderly patients with essential hypertension and LVH may have the basis of abnormal ECG results.…”
Section: Discussionmentioning
confidence: 68%
“…Of note, a retrospective study of individuals with chronic hypertension showed that individuals who had left ventricular hypertrophy by electrocardiogram compared with those who did not had threefold increased odds of superimposed preeclampsia. 14 It is not clear why left ventricular hypertrophy by electrocardiogram is predictive of superimposed preeclampsia when electrocardiogram is not predictive of left ventricular hypertrophy. Future research studies that evaluate rates of superimposed preeclampsia according to electrocardiogram and echocardiogram would be useful to further clarify the association between left ventricular hypertrophy and superimposed preeclampsia.…”
Section: Research Implicationsmentioning
confidence: 99%